Giải thích các bước giải:
Ta có:
$\begin{array}{l}
\frac{{1 - \tan \alpha }}{{1 + \tan \alpha }} = \frac{{1 - \frac{{\sin \alpha }}{{{\rm{cos}}\alpha }}}}{{1 + \frac{{\sin \alpha }}{{{\rm{cos}}\alpha }}}} = \frac{{\frac{{{\rm{cos}}\alpha - \sin \alpha }}{{{\rm{cos}}\alpha }}}}{{\frac{{{\rm{cos}}\alpha + \sin \alpha }}{{{\rm{cos}}\alpha }}}}\\
= \frac{{{\rm{cos}}\alpha - \sin \alpha }}{{{\rm{cos}}\alpha }}.\frac{{{\rm{cos}}\alpha }}{{{\rm{cos}}\alpha + \sin \alpha }} = \frac{{{\rm{cos}}\alpha - {\rm{sin}}\alpha }}{{{\rm{cos}}\alpha + \sin \alpha }}\\
Vay\,\frac{{1 - \tan \alpha }}{{1 + \tan \alpha }} = \frac{{{\rm{cos}}\alpha - {\rm{sin}}\alpha }}{{{\rm{cos}}\alpha + \sin \alpha }}
\end{array}$